Managing Job‐Related Diversity Processes in High‐Reliability Teams in the Emergency Department. (12th December 2020) - Williams, Grace; Irving, Gemma; Wright, April L.; Middleton, Stuart
Abstract: We examine how high‐reliability teams (HRTs) manage job‐related diversity, which refers to differences among team members in skills and experiences relevant to work tasks. Managing job‐related diversity is important in HRTs because of the need for consistent performance in time‐pressured situations with serious consequences for error. In a qualitative study, we observe and interview members of HRTs in a public hospital emergency department in Australia. Our findings reveal a set of six strategies that HRTs in emergency departments use to manage different types of job‐related diversity. Strategies of active explanations and experience‐based task assignment manage educational diversity within HRT team processes. Strategies of deferring to a single leader and balancing delegation and participative leadership manage power diversity. Finally, strategies of sequential specialist involvement and a co‐production mindset manage functional diversity. Our theoretical model of these strategies and their implications for team processes deepen understanding of job‐related diversity in HRTs. Our study contributes to the literature by (1) shining light on managing the double‐edged sword of job‐related diversity in HRTs; (2) opening up insight into differences in diversity management processes between HRTs and traditional teams; and (3) informing debate in the broader teams literature about specific versus generic processes for managing diversity.